2021
DOI: 10.3390/healthcare9111487
|View full text |Cite
|
Sign up to set email alerts
|

Information Disclosure Contents of the COVID-19 Data Dashboard Websites for South Korea, China, and Japan: A Comparative Study

Abstract: Official responses to the COVID-19 pandemic have prioritized information disclosure. Timely and comprehensive information released by the authorities is conveyed mainly through dashboards, which can better inform the public and help them prepare for the pandemic. However, there is limited evidence regarding the COVID-19 dashboard data presentation for South Korea, China, and Japan. This study aimed to describe the current COVID-19 situation in the three countries and compare the information disclosure content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…The integrated framework can be applied and extended to determine the factors affecting COVID-19 tracing applications in other countries. Moreover, the findings of this study could be applied in other health-related mobile applications worldwide [66][67][68][69].…”
Section: Discussionmentioning
confidence: 89%
“…The integrated framework can be applied and extended to determine the factors affecting COVID-19 tracing applications in other countries. Moreover, the findings of this study could be applied in other health-related mobile applications worldwide [66][67][68][69].…”
Section: Discussionmentioning
confidence: 89%
“…Few studies have evaluated the quality of temporal and spatial COVID-19 data visualisation platforms. Zhao and colleagues [ 29 ] conducted a content analysis of dashboards from Japan, China, and South Korea, comparing the number of indicators in each dashboard, and finding the numbers of indicators to be broadly similar. However, they did not undertake a detailed evaluation of quality.…”
Section: Data and Visualisation Platform Qualitymentioning
confidence: 99%
“…Larcker et al (2020) reported that COVID-19 disclosures most frequently took the form of disclaimers to forward-looking statements and were most frequently included in sections on risk and management discussion and analysis (MD&A). Zhao et al (2021) conducted a comparative study on website COVID-19 disclosure between South Korea, China, and Japan. There were numerous significant discrepancies between the major items published and the important indicators made public by each country.…”
Section: Covid-19 Disclosure Practicesmentioning
confidence: 99%